Cardiometabolic risk in non-diabetic metabolic dysfunction-associated steatotic liver disease (MAFLD) patients: insights from the triglyceride-glucose, plasma atherogenic, and cardiometabolic index - Sedat Ciftel; Serpil Çiftel; Ahmed R. Baykan; Serkan Cerrah; Enver Çiftel; Filiz Mercantepe (Archives of Medical Science)
Introduction The objective of our study was to examine the correlation between hepatosteatosis and the triglyceride-glucose index (TyG), plasma atherogenic index (PAI), and cardiometabolic index (CMI) in nondiabetic patients. We also aimed to assess the usefulness of these indices in evaluating cardiometabolic risk in metabolic dysfunction-associated steatotic liver disease (MAFLD).